Pengaruh Kualitas SDM dan Komitmen Organisasi Terhadap Kinerja Guru Dengan Lingkungan Kinerja Guru Sebagai Variabel Moderasi: Studi Kasus pada Guru SD SE-PT Bangun Jaya Alam Permai Best Agro Internasional - Astriana Simbolon; Yunikewaty Yunikewaty; Fitria Husnatarina (FKIP, Universitas Palangka Raya, 2022)
The purpose of this study was to analyze the influence of the quality of human resources and organizational commitment on teacher performance with the work environment as a moderating variable for elementary school teachers throughout PT Bangun Jaya Alam Permai Best Agro International with the population in this study finding 40 people. The sample is all members of the population using the census method. The analytical tool used in this research is moderated regression analysis. This type of research is quantitative research with a descriptive approach. The data collection technique used is a questionnaire in the form of google to the number of respondents, documentation and literature study and interviews. The results showed that the quality of human resources had a significant positive effect on teacher performance, organizational commitment had a significant positive effect on teacher performance, and the quality of human resources with the work environment had a positive and significant effect on teacher performance and organizational commitment. Work as a moderating variable and significant effect on teacher performance. The results of this study indicate that the quality of human resources, organizational commitment and work environment have a positive impact and can improve the performance of elementary school teachers in PT Bangun Jaya Alam Permai Best Agro International